TI_GERICHTE 14.2011.215 vom 20. Dezember 2011 , Reclamo contro la dichiarazione di fallimento. Nova in senso proprio - TI Tribunale d'appello (2011)
Reclamo contro la dichiarazione di fallimento. Nova in senso proprio